Adaptive state-observer for monitoring flexible nuclear reactors. (15th March 2019) - Dong, Zhe; Liu, Miao; Guo, Zhiwu; Huang, Xiaojin; Zhang, Yajun; Zhang, Zuoyi
Abstract: Since nuclear power still fulfills nearly 11% of world electricity demand nowadays, the flexible operation of nuclear reactors can be positive to improve the penetration level of intermittent renewable energy (IRE) sources. Meanwhile, the operational flexibility of nuclear reactors results in the frequent variation of reactor process variables such as the neutron flux, fuel temperature and primary coolant pressure and temperature, which may fasten the degradation of equipment, and further leads to the necessity of developing performance monitoring methods for nuclear reactors in the context of fast and deep IRE penetration. Motivated by the importance of performance monitoring, an adaptive state observer (ASO) for nuclear reactors is newly proposed, which only needs the measurements of neutron flux and coolant temperature at reactor inlet and can provide globally asymptotic estimation for the normalized concentrations of delayed neutron precursors, 135 Xe and 135 I, the average temperatures of fuel elements and primary coolant as well as the total reactivity disturbance. The ASO is then applied for reconstructing the unmeasurable state variables and total reactivity disturbance of a nuclear heating reactor (NHR). Numerical simulation results verify the theoretical analysis, and show the satisfactory observation performance with its influence given by the ASO parameters. Furthermore, a hardware-in-loop (HIL) verification experiment is performed, and the corresponding results show that this newly-built ASO is not sensitive to the measurement noises, which leads to the feasibility of deploying the ASO on those digital control system platforms. Highlights: Deep penetration of renewables to the grid needs the flexibility of nuclear power. Monitoring is necessary for the reliability of flexible reactors for grid balancing. An adaptive state observer (ASO) of nuclear reactors is given for state monitoring. Globally convergent estimation of states and disturbance can be provided. The performance of ASO is verified through numerical and HIL experiments.